The subject of philosophy in the context of the wisdom. - Вандышев, В. Н. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2016)
An important world philosophical problems, problem of grounds of philosophizing in the context of essence of wisdom, is examined. It is rotined that a dominating in the modern world information-technocratic association is not instrumental in claim of wisdom and appearance of sages in that sense, in what it appeared the thinkers of the Ancient world. Сoncept "wisdom" in modern philosophy practically is not mentioned, it was almost fully worn away from the field map of philosophy. It did not show oneself paradoxical, but exactly such character and for a concept the "soul" there is not a place in psychology. But history of development of world culture testifies that both these concepts were such the meaningful disciplines indicated historically lined up round that! In the context of the examined theme however does a question remain open: does "Add existence of informative network of the Internet of wisdom to the users and assists appearance of sages"? There are different reactions on like development of events. Critics assert that present conversations concerning revolution in area of information technologies and "new economy" are absurd, or, at least, very exaggerated.